Magnet Cities : Migration and Commuting in Romania - Cristea, Marius; Mare, Codruța; Moldovan, Ciprian; China, Andreea-Mirela; Farole, Thomas; Vințan, Adina; Park, Jane; Garrett, Keith Patrick; Ionescu-Heroiu, Marcel (World Bank, Bucharest, 2017)
Romania is the fastest growing economy in the European Union (EU), and Bucharest and Romania’s secondary cities have been its main growth engines. However, while Bucharest has reached productivity levels comparable to those of other EU capitals, secondary cities in Romania still have some ways to go before competing on equal footing with secondary cities in the EU. Without strengthening these secondary cities, the Romanian economy cannot sustain growth in the coming years. The most competitive secondary cities are those that are most astute at attracting people, investments, and tourists. This report looks at the cities that have been most successful at attracting migrants and commuters, and proposes a number of recommendations aimed at making secondary cities more attractive and competitive. The report is primarily addressed to policy makers and to a lay audience interested in urban development issues.This report is structured along four main sections: 1) An analysis of development dynamics, with a particular focus on the importance of cities in driving growth and development; 2) An analysis of migration and commuter patterns in Romania; 3) An analysis of the cities and areas that have been most successful at attracting people, and an analysis of the urban areas that will likely attract most people in the future. 4) Recommendations on how EU, national, and local policies and investments can help make secondary cities more competitive.